Reiny I posted a question earlier (about 3:00) and I have a question about your solution. How did you get -4x? I came up with -8x which does not allow for anymore reduction. Please let me know how you did it. Thanks!
2 answers
You had a -6x on the left, and a -2x on the right side. Add 2x to each side, giving on the left -4x and on the right zero.
x^3 + 3 x^2 -2 x^2 - 6 x + 2 x^2 + 2 x = 0
note that -6x + 2 x = -4x
x^3 + 3 x^2 -4 x = 0
x ( x^2 + 3 x - 4) = 0
note that -6x + 2 x = -4x
x^3 + 3 x^2 -4 x = 0
x ( x^2 + 3 x - 4) = 0